2011
DOI: 10.1021/ie2014982
|View full text |Cite
|
Sign up to set email alerts
|

Transesterification of Dimethyl Carbonate with Ethanol To Form Ethyl Methyl Carbonate and Diethyl Carbonate: A Comprehensive Study on Chemical Equilibrium and Reaction Kinetics

Abstract: This article studies the consecutive transesterification of dimethyl carbonate with ethanol to form ethyl methyl carbonate and diethyl carbonate. The chemical equilibrium and reaction kinetics of this system are investigated experimentally and theoretically. To enhance the reaction rate, the homogeneous catalyst sodium ethoxide was applied. Molar-based and activity-based chemical equilibrium constants were calculated from experimental results, and their temperature dependence was described using the van't Hoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…In one of our previous articles, we found that a small amount of water brought in by the chemicals reacts with the catalyst sodium ethoxide to form sodium carbonate (Keller et al, 2011a). The molar fraction x cat of the homogeneous catalyst sodium ethoxide inside the column should always be higher than x cat,min = 4·10 -4 mol/mol to compensate for its consumption.…”
Section: Objective and Penalty Functionsmentioning
confidence: 92%
See 3 more Smart Citations
“…In one of our previous articles, we found that a small amount of water brought in by the chemicals reacts with the catalyst sodium ethoxide to form sodium carbonate (Keller et al, 2011a). The molar fraction x cat of the homogeneous catalyst sodium ethoxide inside the column should always be higher than x cat,min = 4·10 -4 mol/mol to compensate for its consumption.…”
Section: Objective and Penalty Functionsmentioning
confidence: 92%
“…The second step is the transesterification of EMC with EtOH to form DEC and MeOH (R2). In our previous work, we found that sodium ethoxide is a suitable homogeneous catalyst to enhance the reaction rate (Keller et al, 2011a). The catalyst sodium ethoxide was used to experimentally determine the chemical equilibrium and reaction kinetics of the transesterification of DMC with EtOH.…”
Section: Reaction Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The second model constitutes another potential kinetic model that considers partial first order for both components, as previously proposed in the literature for a similar transesterification reaction between DMC and ethanol in the presence of sodium ethoxide [38].…”
Section: Proposal and Discrimination Of Kinetic Modelsmentioning
confidence: 99%